Vernacular Tantra? An Analysis of the Bengali Text The Garland of Bones. (20th May 2021) - Ondračka, Lubomír
Abstract : The paper introduces the Middle Bengali text The Garland of Bones (Haramala) into Western scholarship, and poses the question of what milieu it was produced and transmitted in. The main subject matter of this work is Tantric yoga, particularly the concept of the body. Content analysis reveals that it draws from different known sources (East Indian Kaula Sanskrit Tantras and vernacular works), but also contains a substantial amount of material that seems to be unique. Although the study of this text is full of uncertainties, and several questions related to it remain unanswered, the paper concludes that The Garland of Bones was probably composed in seventeenth-century Chittagong in a vernacular Tantric milieu, which was separate from the mainstream Sanskrit-oriented Kaula tradition. Later, probably in the eighteenth century, the text was adopted by the householder Naths in the eastern parts of undivided Bengal, and became one of their most important scriptures.